2007
DOI: 10.1073/pnas.0704695104
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide transformation of yeast reveals mismatch repair complexes to be differentially active on DNA replication strands

Abstract: Transformation of both prokaryotes and eukaryotes with singlestranded oligonucleotides can transfer sequence information from the oligonucleotide to the chromosome. We have studied this process using oligonucleotides that correct a ؊1 frameshift mutation in the LYS2 gene of Saccharomyces cerevisiae. We demonstrate that transformation by oligonucleotides occurs preferentially on the lagging strand of replication and is strongly inhibited by the mismatch-repair system. These results are consistent with a mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
61
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 55 publications
7
61
0
Order By: Relevance
“…8 On the other hand, Msh6-deficiency only allowed the introduction of 1-, 2-, 3-and 4-nt substitutions, while nucleotide insertions were still suppressed by the activity of the remaining MSH2/MSH3 complex. 8 Similarly, Kow et al 50 reported that +7 nt insertions could efficiently be introduced into an msh3-deficient yeast strain, while +1 nt insertions were suppressed by residual MSH2/MSH6 activity. Conversely, msh6-deficient cells were permissive for +1 nt insertions, while +7 nt insertions were suppressed.…”
Section: Suppression By Mmr Depends On the Type Of Sequence Alterationmentioning
confidence: 97%
“…8 On the other hand, Msh6-deficiency only allowed the introduction of 1-, 2-, 3-and 4-nt substitutions, while nucleotide insertions were still suppressed by the activity of the remaining MSH2/MSH3 complex. 8 Similarly, Kow et al 50 reported that +7 nt insertions could efficiently be introduced into an msh3-deficient yeast strain, while +1 nt insertions were suppressed by residual MSH2/MSH6 activity. Conversely, msh6-deficient cells were permissive for +1 nt insertions, while +7 nt insertions were suppressed.…”
Section: Suppression By Mmr Depends On the Type Of Sequence Alterationmentioning
confidence: 97%
“…Our results are most consistent with a mechanism in which the oligo anneals to either the leading or lagging strand of replication at the replication fork, with subsequent extension. Mispairs created by the oligos are recognized by MMR, but those mispairs that escape MMR recognition create mutations in the next round of replication (6). For the experiments reported here, we used a mutation in an essential codon of the yeast TRP5 gene, the reversion of which occurs solely by restoration of the original codon (7).…”
mentioning
confidence: 99%
“…Evidence suggests that ssODNs anneal to their complementary target DNA when it is transiently single-stranded during replication. However, MMR represses the efficiency of ssODN-mediated gene modification, thereby severely limiting its applicability (14,20,21). Different strategies have been reported to overcome the repressive action of MMR, which include permanent MMR disruption, transient knockdown of MMR activity, and the use of base analogs that attenuate recognition of mismatches by MMR (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian, yeast, and prokaryotic cell systems, it has unequivocally been demonstrated that the DNA mismatch repair (MMR) system has a strong suppressive effect on oligo targeting efficiencies (14,20,21). Disabling the MMR system through disruption of the key MMR gene Msh2 increased the targeting efficiency up to 700-fold in mouse embryonic stem cells (mESCs) (20).…”
mentioning
confidence: 99%